2016
DOI: 10.1002/chem.201604904
|View full text |Cite
|
Sign up to set email alerts
|

Direct Catalytic Hydrogenation of Simple Amides: A Highly Efficient Approach from Amides to Amines and Alcohols

Abstract: A highly chemoselective and reactive direct catalytic reduction of various amides to amines and alcohols was developed by using a tetradentate ruthenium complex. The catalytic system showed excellent activity (turnover numbers up to 19 600) and great functional group tolerance under mild reaction conditions, compared to several bidentate and tridentate ruthenium-catalyzed systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 37 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…In the meantime, remarkably high TON of 8800 was observed in the hydrogenation of 3a catalyzed by a ( P , N py , N H, P )Ru complex, albeit with much higher P H2 ( P H2  = ca. 5 MPa, t  = 20 h) 36 .
Figure 2Precatalysts tested and diverse catalysts derived from 1a . ( a ) Hydrogenation of 3a using different Ru-complexes 1a – f and 2a ([Ru] 0  = 3.3 mM) as precatalysts.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meantime, remarkably high TON of 8800 was observed in the hydrogenation of 3a catalyzed by a ( P , N py , N H, P )Ru complex, albeit with much higher P H2 ( P H2  = ca. 5 MPa, t  = 20 h) 36 .
Figure 2Precatalysts tested and diverse catalysts derived from 1a . ( a ) Hydrogenation of 3a using different Ru-complexes 1a – f and 2a ([Ru] 0  = 3.3 mM) as precatalysts.
…”
Section: Resultsmentioning
confidence: 99%
“…In any event, the H 2 -adsorption site with bulky i Pr (or Cy) groups is non-innocent and undergoes meaningful structural changes via multiple hydrogen additions before producing the diverse, active forms of catalyst. These results further suggest that a Ru complex bearing a ( P ,( N , N ) bpy , P ) ligand is more versatile and robust in the production of diverse catalysts than Ru precatalysts bearing simple bidentate ( P , N py ) 38, 40 and ( P , N H) 1821, 2628, 37 , tridentate ( P ,( N , N ) bpy ) 2225 , and tetradentate ( P , N py , N H, P ) 36 ligand(s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,anumber of catalytic systems have demonstrated that ruthenium pincerc omplexes could function as advantageous catalysts in the directh ydrogenation of linear amides for the synthesis of the corresponding amines and primary alcohols. [10][11][12][13] Under mild reaction conditions, ruthenium pincer complex 1 (Ru-MACHO, Scheme 1), ac ommercially available bifunctional catalyst, has exhibited extremelyh igh catalytic activity in the hydrogenation of ketones, amides, and carboxyl esters in the presenceo fasuitable strong base. [14] In contrast, hydride analogue 2 (Ru-MACHO-BH,S cheme 1b) does not require as trong base for activation in similarh ydrogenation reactions,d ue to lack of ac hloride ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Among them, reduction of carboxamides, commonly mediated by metal hydrides,i so ne of the most frequently used processes that potentially delivers three possible products:a ldehydes,a lcohols,a nd amines (Scheme 1A). In contrast, alcohols or amines could be formed when I fragments through either CÀNo rC ÀOb ond scission, respectively,a nd the resulting aldehydes or imine/iminium intermediates are reduced by the second hydride.Atpresent, the state-of-the-art approaches for reduction of amides to alcohols are catalytic hydrogenation by well-defined pincer complexes,b ased on Ru, Fe,a nd Mn, under ah ighly pressurized H 2 atmosphere, [4] whereas those for the production of amines are facilitated by either hydrosilylation [5] with various metals [6] or organoboranes [7] as catalysts or electrophilic activation of amides with triflic anhydride. In contrast, alcohols or amines could be formed when I fragments through either CÀNo rC ÀOb ond scission, respectively,a nd the resulting aldehydes or imine/iminium intermediates are reduced by the second hydride.Atpresent, the state-of-the-art approaches for reduction of amides to alcohols are catalytic hydrogenation by well-defined pincer complexes,b ased on Ru, Fe,a nd Mn, under ah ighly pressurized H 2 atmosphere, [4] whereas those for the production of amines are facilitated by either hydrosilylation [5] with various metals [6] or organoboranes [7] as catalysts or electrophilic activation of amides with triflic anhydride.…”
mentioning
confidence: 99%